Legal Position Of The Property Separation Agreement In Marriage Against The Confiscation Of The Husband's Property By The Court - Habibie, Dieva Ahmad; Rhamdani, Dwi Aryanti (UNIVERSITAS PAKUAN, 2025)
Abstract This study aims to examine the legal position of the property separation agreement in marriage, as stipulated in Article 29 of Law Number 1 of 1974 concerning Marriage, especially related to the confiscation of marital property by the court, as well as evaluate the extent to which legal protection can be provided for the property. The type of research used is normative juridical with descriptive-analytical nature, using a legal approach and a case approach. Data collection techniques are carried out through literature studies, then data management is analyzed qualitatively. The findings of the study show that the property separation agreement has significant legal force in separating the inherited property of each party, but in the implementation of confiscation by the court, inconsistencies are often found caused by differences in legal interpretation and judicial practice. Therefore, this study emphasizes the need for stricter and more consistent law enforcement to protect the ownership rights of inherited property that has been separated, so that there is no unlawful confiscation and innocent parties can obtain optimal legal protection. Keywords: Property Separation Agreement, Property Confiscation, Inherited Property, Legal Protection.